Household repayment default: evidence from Amanah Ikhtiar Malaysia in Kelantan / Wan Nur Fatin Hidayah Noor Azaha - Noor Azaha, Wan Nur Fatin Hidayah (Faculty of Business Management, 2018)
This paper intended to measure the knowledge of business, characteristics of loan and household behaviour towards default in repayment. Amanah Ikhtiar Malaysia was established with the purpose to provide small capital without collateral. Even though AIM was established to provide financing for poor and hardcore poor household, this does not mean this organization is free from default payment. Previous study had been shown that 50% of borrowers borrow the money but they did not generate the profit from the loan which will increase default in repayment (Abdullah et al, 2011). The study focus to people who participated in AIM Kelantan and 150 questionnaires had been distributed among them. As for this research, descriptive analysis had been used to get the summarization characteristics of a collected data. The regression, correlation and reliability analysis had been used to achieve the objectives. The data were analysed using regression through IBM SPSS Statistics VV22.0. The findings showed, knowledge of business was significant relationship to the factor that influence the household repayment default while characteristics of loan and household behaviour were rejected.